Protective Effect of Blood Cora Polysaccharides on H9c2 Rat Heart Cells Injury Induced by Oxidative Stress by Activating Nrf2/HO-1 Signal Pathway - Jiang, Yong; Zhou, Wei; Zhang, Xin; Wang, Ying; Yang, Dingyi; Li, Shujie (Frontiers in Nutrition, 2021)
The protective effect of blood cora polysaccharides (BCP) on H9c2 rat heart cells under oxidative stress was explored with the use of a H9c2 cell oxidative stress model. The ability of BCP to scavenge 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 1,1-diphenyl-2-picrylhydrazyl (DPPH), and hydroxyl radicals and its reducing power were measured in vitro, indicating a more powerful antioxidant effect of BCP compared to a similar concentration of vitamin C. The cellular metabolic activity was tested through the MTT (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide) assay. Additionally, the relevant oxidation indicator level within the cell supernatant and cells was tested with reagent kits, and mRNA and protein expression levels in the cells were tested through quantitative polymerase chain reaction (qPCR) and western blot. The chemical composition of BCP was determined through high performance liquid chromatography (HPLC). The results show that compared with the normal group, the model group's cell survival rate (28.75%±2.56%) decreased, lactate dehydrogenase (LDH) leakage and the malondialdehyde (MDA) content increased, and superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) levels decreased. The results of qPCR and western blot show that compared with the normal group, the model group's Bcl-2 associated X protein (Bax), caspase-3, nuclear factor erythroid-2 related factor 2 (Nrf2), heme oxygenase-1 (HO-1) expression, NAD(P)H:quinoneoxidoreductase 1 (NQO1), and cytochrome c (Cyt C) decreased, and B-cell lymphoma-2 (Bcl-2) expression was increased, with significant statistical differences. Compared with the model group, the cell survival rate for each BCP-treated group increased, the LDH leakage decreased, the SOD, CAT, and GSH levels in the cells increased, the MDA content decreased, the Bax, caspase-3, Nrf2, HO-1, NQO1, and Cyt C expression was weakened, and the Bcl-2 expression was strengthened. BCP inhibited the reduction of mitochondrial membrane potential caused by H2O2 treatment. According to the component analysis, BCP mainly consist of mannitol, ribose, glucosum anhydricum, galactose, and xylose. It was observed that the Nrf2/HO-1 signaling pathway can be activated, regulated, and controlled by functional BCP to protect H9c2 cells injured by oxidative stress.